THE EFFECTIVENESS OF PROJECT BASED LEARNING TO THE TEACHING OF READING COMPREHENSION - Hambali, Uyunnasirah; Rahman, Muhammad Asfah; Atmowardoyo, Haryanto (Study Program of English Literature, 2019)
The research objectives were to find out whether (or not) the use of Project Based Learning can improve the reading comprehension of the second grade students of SMK Muhammadiyah 4 Tallo Makassar, and to know whether (or not) the use of Project Based Learning Strategy can improve the reading interest of the second grade students of SMK Muhammadiyah 4 Tallo Makassar. This research applied quasi experimental design. The population of this research was the second year students of SMK Muhammadiyah 4 Tallo Makassar in academic year 2015/2016. This research used cluster random sampling. The sample of this research consisted of 72 students belonging two classes, 36 students in experimental group and 36 students in control group. The instrument of the research was used to collect the data in this research, those are reading comprehension test and questionnaire. The data were analyzed by using independent samples test and inferetial statistics on SPSS version 20.0. The result of posttest of experimental group is more significantly improved than the students’ result of posttest of control group by the students’ mean score 83.22. >77.83. The difference of both scores is statistically significant it is based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). the students’ precentage responses from questionnaire show 38.9% very high interest and 52.8% high interest, and 8.3% moderate and the mean score is 81.06. It means, the students are interested in learning reading comprehension by using Project Based Learning strategy.